Optimization of Energy Efficiency with A Green Building Approach in The Mahata Serpong Apartment - Hidayatulloh, Alfian; Nurwidyaningrum, Dyah (POLITEKNIK NEGERI JAKARTA, 2024)
The crisis of non-renewable energy and environmental conservation have become major concerns worldwide. The Indonesian government has responded by launching a national movement to conserve energy. One concrete step taken is the implementation of the Green Building concept, which minimizes resource consumption and maximizes the use of natural resources. In Indonesia, green building assessments are conducted by the Green Building Council Indonesia (GBCI) through the Greenship tool, while internationally, the EDGE application is used for green building certification. For this research use EDGE application for assessing the study case building. This study aims to optimize energy efficiency at Apartemen Mahata Serpong using the EDGE application. The research is expected to reveal the level of energy savings at Apartemen Mahata Serpong and how well the building meets green building criteria. The study begins with data collection, followed by analysis using the EDGE application. The EDGE analysis shows that the existing energy usage at Apartemen Mahata Serpong is 5,88%. After implementing smart meters and a photovoltaic-based renewable energy system, energy efficiency increased to 8,44%. Utility costs also decreased from Rp. 190,377,164 before optimization to Rp. 186,524,222 after optimization.